2004
DOI: 10.1016/j.jpainsymman.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of megestrol acetate in the treatment of anorexia-cachexia syndrome

Abstract: This study aimed to assess the efficacy and safety of megestrol acetate (MA) in anorexia-cachexia syndrome (ACS). Literature and relevant databases were searched for randomized controlled trials of MA to treat ACS in patients with cancer, AIDS, or other pathologies. Data were extracted by two independent reviewers, and meta-analyses were performed where possible. Twenty-six studies were included (n=3,887). Compared to placebo, MA increased appetite in oncology patients [RR=2.31 (95% CI 1.52-3.59)], led to weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(41 citation statements)
references
References 36 publications
0
39
0
2
Order By: Relevance
“…A systematic review demonstrated the safety and efficacy of megestrol acetate in treating cachexia for patients with cancer. 211 However, a second systematic review and meta-analysis of 4 studies revealed no benefit of progestational steroids compared with placebo for treatment of CRF ( z score=0.78; P =.44). 138,212 …”
Section: Interventions For Patients At the End Of Lifementioning
confidence: 99%
“…A systematic review demonstrated the safety and efficacy of megestrol acetate in treating cachexia for patients with cancer. 211 However, a second systematic review and meta-analysis of 4 studies revealed no benefit of progestational steroids compared with placebo for treatment of CRF ( z score=0.78; P =.44). 138,212 …”
Section: Interventions For Patients At the End Of Lifementioning
confidence: 99%
“…Anorexia has been shown to be treatable with androgenic and anabolic steroids including nadrolone, decanoate, and oxandrolone [105107]. …”
Section: Management For Nutrition-related Complicationsmentioning
confidence: 99%
“…In several clinical trials, these compounds have been found to improve appetite and increase body fat-free mass [15,16].…”
Section: Progestational Drugsmentioning
confidence: 99%